PENGARUH KOMITMEN ORGANISASI DALAM MEMEDIASI KEPEMIMPINAN TRANSFORMASIONAL TERHADAP PERILAKU INOVATIF TENAGA PEMASARAN PT. TIRA AUSTENITE - Ardi Kusmara (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2021)
This research aimed to to investigated the role organizational commitment in mediating the effect of transformational on innovative behavior. Survey method used in this research. Amount of the samples in this research are 67 sales of at PT. Tira Austenite that selected randomly. The data were collecting through questionnaire and analyzed by using path analysis. The results of the research can be concluded that: transformational leadership and organizational commitment have a direct effect on innovative behaviour; transformational have a direct effect on sales innovative behavior and transformational leadership have an indirect effect on innovative behaviors through organizational commitment.